(untitled) (Journal of Medicine, 2012)
Background: Pregnancy related acute renal (PRARF) failure is more common in developing countries than developed country. Improved antenatal care and obstetric care reduce PRARF in developed country. In Bangladesh maternal mortality rate is 3.8/1000 population of which 25% account for acute renal failure. We try to find out cause, risk factor and out come of pregnancy related acute renal failure. Materials and Methods: A prospective observational study was done to observe the status of ARF in pregnancy in Nephrology Department of Dhaka Medical College during 2007-2008. All patients were undergone detail history, clinical examination and investigation and follow up during hospital stay. Data recorded in predesigned case record form. Statistical analysis was done with SPSS soft ware 12.5 package. All data presented as mean or percentage. The Chi square test or Fishers exact test was used to compare differences in the frequency of clinical manifestations among cases. P value <0.05 count as significant. Results: Among 57 women, the mean age was 27±6.6 years range from 17-43 years. Sixty seven percent were multrigravidae, 51% (29) was on irregular antenatal care, and 67% below primary level of education. Renal failure occur mainly in 3rd trimester of pregnancy (31.4±7.4 weeks). Common presentation is with generalized swelling (51%)and oligouria (52%) with reduce haemoglobin and leucocytosis. The mean creatinine was 6.7±3mg/dl in this series. Lower uterine caeserian section (LUCS) done in 23% cases. 56.1% had severe renal failure and 47% patients required dialysis. Complete recovery was seen in 63% cases while, 31% died and 6% patient have incomplete recovery with persistent dialysis dependent status. Septicaemia (43%) and eclampsia (19%) were the main cause of PRARF, others causes were PPH, APH, ruptured ectopic pregnancy. In 3% patients, actual cause was not identified. Poor antenatal care (p-0.027 ), severity of renal failure (p-0.066), patient requiring dialysis (p-0.025), LUCS (0.028), septicaemia (p-0.026) and low level of education (0.036) have significant effect on outcome. Conclusion: Pregnancy related acute renal failure is common with increased mortality in our study due to poor antenatal care, low level of education and multiple pregnancy. Improve obstetrical care and Nephrological care may reduce Pregnancy related acute renal failure and mortality. DOI: http://dx.doi.org/10.3329/jom.v13i2.12739 J Medicine 2012; 13 : 129-132